Child Sacrifice, Conquest and Cosmic War: On the Harmful Habitation of Biblical Texts. (April 2017) - Rowley, Matthew Patrick
Killing in the name of God is complex and someone could arrive at the conclusion that God participates in their actions through a variety of channels. This article examines one common practice among many who believe their killing pleases or is willed by God—inhabiting biblical texts. Focusing on the Abrahamic and Mosaic narratives and on eschatology, I will explain part of the process whereby individuals and groups come to believe that they are participating in killing patterned on or prophesied in scripture. Finally, this article will suggest a scripture-based approach aimed at moving an individual or group away from the harmful habitation of sacred texts.